Idololatria Vilnensis: The Confessional Debates of Jesuits and Protestants on Sacred Images in the 16th Century Lithuania - Riklius, Tomas (Literatūra, 2025)
Despite the abundance of theological treatises in the Grand Duchy of Lithuania in the late 16th century, only five of the eighty-six known titles deal with the use of sacred images and reveal the opposing sides of Catholics and Protestants in such confessional debates. The Protestant perspective is represented by Andrzej Wolan’s 1583 treatise ‘An Attack on the Idolatry of the Loyolites of Vilnius’, which relies primarily on theological arguments to criticise the Catholic practice of using sacred images. Wolan’s critique, while rooted in theology, also touched on the Renaissance humanist perspective on aesthetics to question the sensual appeal of Catholic sacred art. In response, the Catholic theologian Andrzej Jurgiewicz defended the use of sacred images, emphasising their role as visual witnesses of Catholic tradition in a post-Tridentine aesthetic paradigm. This article analyses these theological and aesthetic arguments of Wolan and Jurgiewicz found in treatises representing Catholic and Protestant positions in the polemical debates on the use of sacred images in the Polish-Lithuanian Commonwealth in the late 16th century.